Interprofessional Collaboration Factor Analysis in Affecting Tropical Disease Services at Kambaniru Health Center, Waingapu Health Center, Kanatang Health Center 2017 - Oklan B.T Liunokas (Poltekkes Kemenkes Kupang, 2018)
Background: Healthcare services is a form of health care that has no legal basis is 1945 constitution of every individual in obtaining adequate protection for survival. Collaboration / cooperation between the professions in the health service is actually very useful for the achievement of the health program, both individuals and families to achieve the level of health. Methods: This type of research using a survey method, the analytic design. The population in this study were health workers in health services in the Region Sumba, which is taken from the clinic Kambaniru, Waingapu and Kanatang located in the County of East Sumba. with a sample of 109 people. Research and data collection was conducted from April to August 2017. Results: The results of the analysis of the relationship between knowledge and interprofessional collaboration were obtained by Pearson Chy Square = 4,628a Asymp. Sig (2-sided) 0.039 <0.05 means that the value of p <α (0.05) then this analysis shows that knowledge has a significant influence with interprofessional collaboration. The analysis results of odds ratio = 3.13 means that respondents who lack knowledge will have 3 times the risk of not running interprofessional collaboration compared to those with good knowledge.